2016
DOI: 10.1016/j.jaac.2015.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Access to Psychosocial Services Prior to Starting Antipsychotic Treatment Among Medicaid-Insured Youth

Abstract: A majority of Medicaid-insured youth initiating antipsychotic treatment have not received a psychosocial service in the preceding 3 months. This service pattern highlights a critical gap in access to psychosocial services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 40 publications
1
18
1
Order By: Relevance
“…Most young children receiving care for ADHD (65%) were in utilization profiles characterized by low or no probability of psychological services and high probability of receiving ADHD medication. These results are consistent with previous research that showed that less than one-half of young children received any psychosocial treatment before being treated with antipsychotic medications (15). The variation in treatment receipt across these seven states is also consistent with previous studies showing differences in state-level estimates of medication and behavioral treatment among children with ADHD (14, 18).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Most young children receiving care for ADHD (65%) were in utilization profiles characterized by low or no probability of psychological services and high probability of receiving ADHD medication. These results are consistent with previous research that showed that less than one-half of young children received any psychosocial treatment before being treated with antipsychotic medications (15). The variation in treatment receipt across these seven states is also consistent with previous studies showing differences in state-level estimates of medication and behavioral treatment among children with ADHD (14, 18).…”
Section: Discussionsupporting
confidence: 93%
“…The misalignment between clinical guidance and utilization could be the result of a number of factors. Provider availability may be a key driver, because few trained professionals are available to deliver evidence-based psychosocial treatments for children (15). There may be differences by physician type in care of children with ADHD (30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other similarities to their study are the low incidence of prior treatment with cognitive behavioral interventions and the fact that younger children were less likely to have received prior treatment. In contrast to our findings, in over half of a sample of Medicaid insured children, there was no prior psychosocial treatment in the 3 months before the antipsychotic had been prescribed [32,38]. However, our study, as well as the study by Rettew et al [7] assessed all prior lifetime treatments, which might explain this difference.…”
Section: Discussioncontrasting
confidence: 95%